2002
DOI: 10.1074/jbc.m203695200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domain Required for Catalytic Activity of Auxilin in Supporting Clathrin Uncoating by Hsc70

Abstract: During clathrin-mediated endocytosis Hsc70, supported by the J-domain protein auxilin, uncoats clathrin-coated vesicles. Auxilin contains both a clathrinbinding domain and a J-domain that binds Hsc70, and it has been suggested that these two domains are both necessary and sufficient for auxilin activity. To test this hypothesis, we created a chimeric protein consisting of the J-domain of auxilin linked to the clathrin-binding domain of the assembly protein AP180. This chimera supported uncoating, but unlike au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…Thus, Hsc70 and auxilin are slowly dissembling the clathrin lattice, rather than causing catastrophic collapse of the pits. These findings are consistent with our previous observations that, individual triskelions are able to be uncoated from clathrin baskets when a chimera of AP180 and auxilin is used (Ma et al, 2002).…”
Section: Resultssupporting
confidence: 83%
“…Thus, Hsc70 and auxilin are slowly dissembling the clathrin lattice, rather than causing catastrophic collapse of the pits. These findings are consistent with our previous observations that, individual triskelions are able to be uncoated from clathrin baskets when a chimera of AP180 and auxilin is used (Ma et al, 2002).…”
Section: Resultssupporting
confidence: 83%
“…Using a simple perpendicular light-scattering assay we have measured the in vitro disassembly of clathrin cages by Hsc70 and auxilin, which occurs rapidly with a t 1∕2 of approximately 10 s. This is comparable to recent results from experiments that used dynamic light scattering to monitor clathrin cage disassembly (21,22) but faster than earlier centrifugation-based studies that had t 1∕2 values ranging from 2-10 min (19,20,24) but that also contained adaptor proteins such as AP180 or AP2, which are known to stabilize the cages and may consequently have slowed down disassembly. In this study, we have increased the time resolution beyond that of dynamic light scattering by monitoring perpendicular light scattering, and analysis of these data has allowed us to isolate and describe individual steps in the chaperone-mediated disassembly of cages that hitherto have remained invisible.…”
Section: Discussionsupporting
confidence: 69%
“…Previous binding studies have shown a maximal binding of three Hsc70s per triskelion at equilibrium (16,24), and, like in our study, this was shown to occur with only a single auxilin per triskelion. It has also been shown that approximately three molecules of Hsc70 dissociate one triskelion when coated vesicles rather than empty cages were used (6) and it has been found that, following disassembly, three Hsc70s are bound to each free triskelion (14,15).…”
Section: Discussionmentioning
confidence: 48%
“…The clathrin-binding domain of auxilin (amino acids 547-813) is bipartite and consists of two subdomains comprising either predominantly clathrin N-terminal or distal domain interaction sites (15). Recently, Ma et al (16) constructed a chimeric protein from a C-terminal fragment of murine AP180 (residues 325-915) and the J-domain of auxilin. With this chimera, they were able to demonstrate that binding of a J-domain protein to the N-terminal domain of the clathrin heavy chain is sufficient to recruit hsc70 and to facilitate the dissociation of clathrin cages to a certain degree.…”
mentioning
confidence: 99%